Persepsi golongan muda terhadap kraftangan - Tengku Nor Haziyah, binti Tengku Dahlam (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study is a survey conducted to young people about the handicraft. The objective of this a study conducted for the young about the handicrafts. The main purpose of this research study is to identify the interaction and behavior of young people towards handicraft. A total of 200 respondents from of young people were randomly selected as the sample study. This research method is descriptive in nature of the quantitative method through questionnaires as of study instrument and were analyzed using statistic packages for social sciences (SPSS) version 19.0. The design of the questionnaire is divided into three parts namely part A, part B and part C. The questionnaire also will be distributed to a sample of the young people. The analysis is presented in the form of percentage and frequency. The data collected will also be studied using the test of cross tabulation. The questionnaires were distributed by the researcher to the respondents are answered and achieve the objectives of this research on of young people’s perception of the handicrafts.